Control of Families at Risk of Stunting through Demographic Approach and Information Dissemination - Pratiwi, Bintang Agustina; Angraini, Wulan; Suryani, Iis; Nurdan, Jon Hendri; Riastuti, Frensi (Poltekita: Jurnal Ilmu Kesehatan, 2024)
Stunting prevention in high-risk families, particularly regarding environmental factors, remains a significant issue in Bengkulu Province as an area characterized by limited access to safe drinking water and adequate sanitation, both key indicators of stunting risk. This study aimed to identify factors associated with the risk of stunting among families in Bengkulu Province, Indonesia. A cross-sectional approach was employed using secondary data from the 2021 Population Survey (PK21) of Bengkulu Province, which included 436,490 families. Univariate, bivariate (chi-square), and multivariate logistic regression analyses were conducted. The results showed that 83.1% of families in Bengkulu Province were not at risk of stunting. Factors significantly associated with stunting risk included the occupation and educational level of the head of household, health insurance status, household income adequacy, housing ownership status, and exposure to information through media and health officers (p < 0.001). Families with heads of household working as farmers and those with heads who did not complete elementary school had the highest prevalence of stunting risk. Families without health insurance, inadequate income, rent-free housing, and no exposure to the Bangga Kencana program through media or officers also exhibited a higher prevalence of stunting risk. Logistic regression analysis revealed that families not receiving Bangga Kencana information from officers were 1.08 times more likely to be at risk of stunting (95% CI = 1.05–11). In conclusion, demographic factors and information exposure were identified as critical risk factors for stunting among families in Bengkulu Province. These findings highlight the importance of targeted interventions and information dissemination in reducing stunting risk.